Evaluation of exotic potato genotypes for resistance to late blight - VINAY BHARDWAJ, SANJEEV SHARMA; B.P. SINGH, A.K. SRIVASTAVA, T.K. BAG, M.S. GURJAR* (Indian Phytopathology, 2015)
Eighty-eight accessions of potato (Solanum tuberosum L.) imported from 15 countries were evaluated for resistance to late blight at Central Potato Research Station, Shillong, during 2006-2010. Under laboratory testing, seven lines were found resistant, 11 moderately resistant and 70 susceptible, while under field testing under natural epiphytotic conditions, 10 accessions were found to be resistant, 18 moderately resistant and 60 susceptible to late blight. Fifty-nine lines exhibited late blight resistance at par while the rest showed different reactions under both laboratory and field testing. The average relative AUDPC value ranged from 11.86 (CP 2163) to 83.14 (CP 2294) among exotic accessions, while it was 10.5 in resistant check, Kufri Girdhari. Potato accessions, viz. CP 1722, CP 2000, CP 2011, CP 2163 and CP 2379 which showed resistance to late blight both under laboratory and field conditions were shortlisted. These accessions possess acceptable tuber traits having medium to profuse flowering with high pollen fertility. These can be used as donor parents for incorporating late blight resistant genes to develop new potato varieties.